Ciri Khas Eskatologi Injil Lukas - Agus Prasetyo (Sekolah Tinggi Teologi Kalimantan, 2021)
The Gospel of Luke is a complete gospel in the process of compilation. In the material compiled, this research describes the topic of eschatology which was a controversial topic at that time. Even the controversy over eschatological interpretation has continued throughout the centuries. This paper aims to elaborate eschatological thoughts according to Luke's gospel. This paper examines Luke's narratives related to the last days. The research method used by the researcher is to conduct a thematic analysis of Luke's gospel narrative regarding eschatology. In detail, the implementation of the research was carried out in the following stages; the first stage is to look at the purpose of Luke's theology, so that by looking at Luke's goals, the description of the eschatology that Luke reports becomes clearer. In addition to examining the textual evidence of Luke's gospel, this paper also considers the thoughts of New Testament scholars in order to sharpen the interpretations found. As a result, the principle of the development of revelation became the foundation of Luke's eschatological thinking. The peculiarities of Luke's Eschatology can be understood in three aspects, namely the eschatological promise, the beginning of the fulfillment of the promise and the hope of the perfection of the promise. The eschatological promise forms the basis of a sure hope for believers throughout the centuries.Injil Lukas merupakan injil yang lengkap dalam proses penyusunan. Dalam materi yang disusun, penelitian ini menuturkan topik eskatologi yang merupakan topik kontroversial pada masa itu. Bahkan kontroversi tafsir eskatologis terus berlangsung sepanjang abad. Tulisan ini bertujuan mengelaborasi pemikiran-pemikiran eskatologis menurut injil Lukas. Tulisan ini meneliti penuturan-penuturan Lukas berhubungan dengan zaman akhir. Metode penelitian yang dilakukan peneliti adalah dengan melakukan analisa tematik terhadap narasi injil Lukas berkenaan dengan eskatologi. Secara rinci pelaksanaan penelitian dilakukan dengan tahapan sebagai berikut; tahapan pertama adalah melihat tujuan teologi Lukas, sehingga dengan melihat tujuan Lukas, maka gambaran tentang eskatologi yang dilaporkan Lukas menjadi lebih jelas. Selain meneliti bukti tekstual dari injil Lukas, tulisan ini juga mempertimbangkan pemikiran dari para ahli Perjanjian Baru guna mempertajam tafsiran yang ditemukan. Hasilnya, prinsip perkembangan pewahyuan menjadi landasan dalam pemikiran eskatologi Lukas. Kekhasan Eskatologi Lukas dapat dipahami dalam tiga aspek yaitu Janji eskatologis, awal penggenapan janji dan pengharapan kesempurnaan janji. Janji eskatologis menjadi dasar dari sebuah pengharapan yang pasti bagi orang percaya di sepanjang abad.